Penggunaan Daluwarsa sebagai Dasar Gugatan Praperadilan di Indonesia: Antara Formil atau Materiil - Peter Jeremiah Setiawan; Xavier Nugraha; Moch. Marsa Taufiqurrohman (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2020)
This article aims to answer what is the scope of pretrial in statutory regulations and whether expiration can be used as an excuse to file a pretrial lawsuit. By using legal research methods through statutory, conceptual, and case-based approaches, this article concludes that the absence of a clear categorization regarding the formal and material aspects of the expiration case creates a dilemma. In its development, expiration has begun to be recognized as a formal reason which incidentally does not touch the subject matter of the case, an thus can be used as a pretrial excuse. This can be seen in the Pre-trial Decision Number: 143/Pid.Prap/2016/PN.Jkt.Sel. Ultimately, this article suggests the need for a clear regulation in the Perma regarding the categorization of formal and material aspects in pretrial hearings.